2018
DOI: 10.3390/ijms19082410
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Buprenorphine in Major Depression, Treatment-Resistant Depression and Suicidal Behavior: A Systematic Review

Abstract: Although several pharmacological options to treat depression are currently available, approximately one third of patients who receive antidepressant medications do not respond adequately or achieve a complete remission. Thus, novel strategies are needed to successfully address those who did not respond, or partially respond, to available antidepressant pharmacotherapy. Research findings revealed that the opioid system is significantly involved in the regulation of mood and incentives salience and may be an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 58 publications
2
60
0
1
Order By: Relevance
“…Historically, prior to the advent of monoaminergic antidepressants, opioids were used to treat MDD, a practice sometimes referred to as the “opium cure”. 20 More recently, buprenorphine (BUP) has been shown in clinical trials to possess antidepressant activity, particularly in treatment-refractory patients 2024. However, the clinical utility of opioids has been limited by the risk of abuse and dependence 22…”
Section: Introductionmentioning
confidence: 99%
“…Historically, prior to the advent of monoaminergic antidepressants, opioids were used to treat MDD, a practice sometimes referred to as the “opium cure”. 20 More recently, buprenorphine (BUP) has been shown in clinical trials to possess antidepressant activity, particularly in treatment-refractory patients 2024. However, the clinical utility of opioids has been limited by the risk of abuse and dependence 22…”
Section: Introductionmentioning
confidence: 99%
“…κ-Opioid receptors may play an important role in buprenorphine therapeutics, especially for patients with comorbid depression. The antidepressant effects displayed by buprenorphine are related to its antagonistic activity at these receptors [ 39 , 40 ] . Uncontrolled psychiatric illnesses can negatively impact OUD treatment outcomes, and thus, a medication that could potentially provide benefits for both disorders would be clinically advantageous [ 53 , 54 ] .…”
Section: Pharmacogenes: Opioid Receptorsmentioning
confidence: 99%
“…Partial agonism leads to effective analgesic effects and abatement of withdrawal symptoms while reducing the risk of respiratory depression observed with methadone and other opioids [ 20 ] . Additionally, due to its effects on κ-receptors, clinical data have suggested that buprenorphine may possess antidepressant benefits, potentially representing a better option for patients with comorbid depression [ 39 , 40 ] . Buprenorphine has also been co-formulated with naloxone as a sublingual film or tablet to discourage intravenous administration, which results in the immediate onset of euphoric effects [ 20 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The augmentation approach may include antipsychotics, mood stabilizers, anxiolytics, lithium, thyroid hormone, or other drugs. Currently, many new treatment solutions for depressive patients are developed and studied, such as repetitive transcranial magnetic stimulation (rTMS) (8), intravenous/intranasal ketamine (9), inhaled nitrous oxide (10), valgus nerve stimulation (11), deep brain stimulation (12), buprenorphine (13), etc.…”
Section: Introductionmentioning
confidence: 99%